Peningkatan Literasi Keuangan melalui Pengelolaan Keuangan Keluarga untuk Masyarakat Desa Tunggulrejo Kecamatan Jumantono Kabupaten Karanganyar - Kristianto, Djoko; Avianty, Hani Dyah (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2025)
From the initial information, it is known that the people of Tunggulrejo village have not managed their family finances well or some of them have difficulties in managing their finances, including recording family finances. Furthermore, it can be said that the public also does not understand financial literacy. Financial management is one of the main problems in Tunggulrejo village, Jumantono sub-district, Karanganyar district, because if family financial management and understanding financial literacy do not work well it will hinder performance and getting access to financing. The problems that arose during the discussion were the financial attitudes and behavior of their children who are students, university students and single youth in the form of excessive spending behavior, not understanding proper financial planning, and not understanding the priority scale of primary, secondary and tertiary needs. . The team provides solutions regarding the correct meaning of money, saving discipline, and the need to make correct financial planning to achieve individual and family financial resilience. This service has opened the minds and awareness of housewives about the importance of financial literacy in family life. By socializing financial literacy, attitudes and foundations can be fostered in building family financial resilience. Having good financial management will have a positive impact on business continuity, especially for the people of Tunggulrejo village, Jumantono District, Karanganyar Regency.